Non-pharmacologic approaches to treatment of pediatric functional abdominal pain disorders - Chakraborty, Partha Sarathi; Daniel, Rhea; Navarro, Fernando A. (Frontiers in Pediatrics, 2023)
Functional abdominal pain disorders (FAPDs) affect up to 25% of children in the United States. These disorders are more recently known as disorders of “brain-gut” interaction. The diagnosis is based on the ROME IV criteria, and requires the absence of an organic condition to explain the symptoms. Although these disorders are not completely understood, several factors have been involved in the pathophysiology including disordered gut motility, visceral hypersensitivity, allergies, anxiety/stress, gastrointestinal infection/inflammation, as well dysbiosis of the gut microbiome. The pharmacologic and non-pharmacologic treatments for FAPDs are directed to modifying these pathophysiologic mechanisms. This review aims to summarize the non-pharmacologic interventions used in the treatment of FAPDs including dietary modifications, manipulation of the gut microbiome (neutraceuticals, prebiotics, probiotics, synbiotics and fecal microbiota transplant) and psychological interventions that addresses the “brain” component of the brain-gut axis (cognitive behavioral therapy, hypnotherapy, breathing and relaxation techniques). In a survey conducted at a large academic pediatric gastroenterology center, 96% of patients with functional pain disorders reported using at least 1 complementary and alternative medicine treatment to ameliorate symptoms. The paucity of data supporting most of the therapies discussed in this review underscores the need for large randomized controlled trials to assess their efficacy and superiority compared to other treatments.